Blood donation during COVID-19 lockdown and its association with anger and stress: A cross-sectional study from Syria - Kakaje, Ameer; Mansour, Sabina; Ghareeb, Ayham; Hosam Aldeen, Osama (Frontiers in Sociology, 2023)
Background The demand for blood donations in Syria was high as the country has suffered for 9 years from war, and this demand has substantially increased during and after the lockdown from the COVID-19 pandemic. This study aims to assess blood donations in Syria and their association with multiple factors. Methods Online questionnaires were distributed to social media groups, with questions related to stress, anger, and COVID-19 distress. Results This study included 1,423 participants, of which 899 (63.2%) were women. Only 48.5% have ever donated blood, of which 33.3% donated only once in their lifetime. Not having a good reason to donate blood was the main reason for not donating. Obtaining documents was the main reason for blood donation among people who donated blood (64.8%). Stress, anger, and fear of infection were not associated with blood donation and its patterns. Losing someone close and being endangered by war were associated with more frequent blood donations in contrast to being distressed by war. Conclusion COVID-19 distress, stress, and anger were not associated with the decrease in blood donation. Spreading awareness on volunteer blood donation is crucial to combat blood shortage during stressful times.